2021
DOI: 10.1027/1015-5759/a000598
|View full text |Cite
|
Sign up to set email alerts
|

Autism in Aotearoa

Abstract: Abstract. Screening measures for autism spectrum disorder (ASD) are important tools for clinicians and researchers. However, where a measure developed and validated for one population is used with another, its performance in this new context must be carefully examined. The RAADS-14, a brief ASD screen developed in Sweden, was evaluated with a sample of New Zealand adults ( N = 387), 41 of whom self-reported a prior diagnosis of ASD. The convergent validity of the RAADS-14 (Hypothesis 2) was supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…While this paper was in preparation, the results of another study assessing the RAADS-14 properties for a New Zealand national sample were published [31]. The two studies are similar in their purpose and design, and there are notable similarities in the results as well.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While this paper was in preparation, the results of another study assessing the RAADS-14 properties for a New Zealand national sample were published [31]. The two studies are similar in their purpose and design, and there are notable similarities in the results as well.…”
Section: Discussionmentioning
confidence: 91%
“…Sample 2: A sample was recruited using snowball sampling by targeting autismrelated communities to ensure a higher-than-normal ratio of adults with ASD (total n = 509). To provide the initial estimates of the sensitivity of the RAADS-14 Rus in this study, we relied on self-reported ASD diagnosis, reportedly established in clinical settings (n = 49) similar to another recent study assessing the RAADS-14 properties for a different national sample [31]; for a smaller subset of the participants that gave their consent (n = 13), it was further verified using ADOS-2 conducted by a certified specialist. All the participants in this sample used web-based survey forms and completed them at their convenience.…”
mentioning
confidence: 99%
“…While, taken per se, these discriminative properties can be considered operational, it should be noted that using the RAADS-14 Rus as a screening tool with this cut-off would yield a rather low positive predictive value, given the estimated prevalence of high functioning forms of ASD. While this paper was in preparation, the results of another recent study assessing the RAADS-14 properties for a New Zealand national sample were published 30 . The two studies are similar in their purpose and design, and there are notable similarities in the results as well.…”
Section: Correlations With Big Five Personality Traitsmentioning
confidence: 99%
“…Sample 2: A sample with a higher than normal ratio of adults with ASD (total n=509) was recruited using snowball sampling by targeting autism-related communities to ensure a higher than normal ratio of participants with ASD. To provide the initial estimates of the sensitivity of the RAADS-14 Rus in this study we relied on self-reported ASD diagnosis, reportedly established in clinical settings (n=49), similarly to another recent study assessing the RAADS-14 properties for a different national sample 30 ; for a smaller subset of the participants that gave their consent (n=13) it was further veri ed by ADOS-2. All the participants in this sample used web-based survey forms and completed them at their convenience.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%